Roughness-dependent scaling of the contact area and separation gap with pressure for glassy polymers - Utkarsh Patil; Shubhendu Kumar; Stephen Merriman; Ali Dhinojwala (Proceedings of the National Academy of Sciences, 2025)
The contact between two rough surfaces has been a topic of significant interest since early studies on Coulombic friction and remains crucial for numerous technological applications. However, theoretical progress has outpaced experiments due to the challenges in measuring contact areas across scales ranging from subnanometers to macroscopic dimensions. Here, we demonstrate the use of commonly available infrared-based (IR) spectroscopy in combination with finite-difference time-domain (FDTD) optical simulations to measure separation gaps and contact areas for glassy polymers ranging in roughness over two orders in magnitude. With the combined IR and FDTD simulations, we can overcome the optical diffraction limits and take advantage of the chemical specificity of IR spectroscopy to overcome limitations due to scattering. The scaling of the contact area ratio as a function of pressure illustrated the limitations of using pure elastic or plastic deformation in explaining the results. At both low and high pressures, the contact area ratios scale linearly with pressure as expected for purely elastic deformations at low pressures or plastic deformations at high pressures. However, if analyzed over a broad range of pressure, the power laws we observe are much larger than 1, exemplifying the need to consider elastoplastic models in explaining results for softer polymer contacts compared to other brittle, glassy materials. In comparison, the separation gaps scale exponentially with pressure, as expected. These results have important implications for the interpretation of properties such as friction, adhesion, and conductivity for softer, glassy contact interfaces.